ANALISIS MINAT BELAJAR SISWA PADA MATA PELAJARAN IPA SD DAN SMP DI SD SMP SATAP 1 JEROWARU - Fena Prayunisa; Ahmad Dedi Marzuki (Berugak Baca, 2024)
Study This aim For analyze interest Study student on eye elementary and middle school science lessons at SD SMP Satap 1 Jerowaru . Type study This is method study descriptive. Form design used​ in researcher is qualitative. Technique data collection used as tool measuring or instrument covers Teacher interviews and Questionnaire to students, Questionnaires, and Observation to student. Interview used For get related data influencing factors​ interest study science. Questionnaire used For data collection with method submit question written For answered in a way written by students, with questionnaire We Can obtain information from respondents about self personal student or student things​ know. Questionnaire used For get related data profile interest students learn science. Observation used For obtain data related to the learning process in the classroom . Subject study This is all over class V and class VII at Satap Middle School Jerowaru , fifth grade teacher and class VII. Based on Results Questionnaire There are 10% of fifth grade elementary school students who are interested And on There are 15% of class VII junior high school students who are interested . Based on Results Questionnaire There are 15% of fifth grade elementary school students who are interested And on There are 15% of seventh grade junior high school students interested . Based on Results Questionnaire There are 30% of fifth grade elementary school students who are interested And on 20% of class VII junior high school students are sufficient interested . Based on Results Questionnaire There are 45% of fifth grade elementary school students who are interested And on There are 50% of class VII middle school students who are offline interested . So necessity cooperation between teacher and parent as well as environment school For create atmosphere learning fun​ For increase interest Study student especially on science learning . Replace pattern think students who think learning scary become learning fun​